Prevalence of intimidation, harassment, and discrimination in resident physicians: a systematic review and meta-analysis - Bahji, Anees; Altomare , Josephine (Canadian Medical Education Journal, 2019)
Background: The aim of this study was to establish the prevalence of intimidation, harassment, and discrimination (IHD) reported by resident physicians during their training, to identify factors associated with reported IHD, and to identify adverse sequalae associated with IHD. Methods: This review followed the PRISMA guidelines. Eight electronic databases were searched for cross-sectional studies reporting the prevalence of IHD among resident physicians. Prevalence estimates were pooled across studies using random-effects meta-analysis, with variance stabilization using Tukey double arcsine transformation. Heterogeneity was assessed with forest plots, the I2 statistic, subgroup analyses, and multivariate meta-regression. Results: 52 cross-sectional studies were included in the meta-analysis. The overall pooled prevalence of IHD was 64.1% (95% confidence interval [CI], 51.0-77.1). Verbal, physical, and sexual IHD were the most common forms of IHD reported by residents. Training status (55.5%), gender (41.7%), and ethnicity (20.6%) were the most commonly cited risk factors for IHD. The most common sources of IHD were relatives/friends of patients, nurses, and patients (cited by 50.7%, 47.8, and 41.7%, respectively). Conclusions: The prevalence of IHD among resident physicians is high and associated with multiple negative outcomes, including burnout. Despite the availability of multiple anti-IHD interventions, reports of IHD appear to be rising in many residency programs.